Árvore genealógica: visualidades de si para um ensino de artes visais antirracista - Costa, Natália de Araújo (2023)
This dissertation, developed in the Programa Associado de Pós-Graduação em Artes Visuais, da Universidade Federal da Paraíba e Universidade Federal de Pernambuco (PPGAV UFPB/UFPE), focuses on Visual Arts and its educational, cultural, and creative processes, specifically in the research area on Educational Processes in Visual Arts. The overall objective of this study is to investigate possible strategies for an Anti-Racist Visual Arts Education with undergraduate students in Visual Arts at UFPB. To achieve this objective, the dissertation discusses Anti-Racist Education and characterizes Anti-Racist visualities through the work of black women artists. It also raises questions about Anti-Racist visualities with undergraduate students in Visual Arts at UFPB, aiming to foster collective construction of possible paths towards an Anti-Racist Visual Arts Education. This study is framed as an Arts-Based Research (ABR), as it understands that the object of study is constructed simultaneously with the research process, intertwined with the researcher's and participants' memories and experiences. It employs both verbal and visual texts as ways to interpret this experience. The research is grounded in the field of Visual Culture and is woven through "escrevivência," prioritizing subjectivity that relates to visualities labeled as Anti-Racist, open to interpretations and ways of seeing and thinking in order to build a different approach to images. The study concludes that Anti-Racist Education has been a demand of black movements, leading to the enactment of Law No. 10.639/2003. However, the inclusion of content on African and Afro-Brazilian art is not enough to characterize an educational practice detached from the structural racism that still permeates social relations. It points towards a Visual Arts teaching approach that aligns with the production and practices of black women artists who address racism in contemporary Brazilian art. The study also emphasizes that no single image can propose an Anti-Racist Education or an Anti- Racist Visual Arts Teaching on its own. It is the collective action of teachers and students, in dialogue with images, that can unleash the potential of all individuals affected by outdated hierarchical notions based on skin color.